Aspek Hukum Pemberantasan Terorisme di Indonesia - La Sina (Jurnal Risalah Hukum, 2009)
Terrorism was an action that could cause the disorder situation, as well as caused damage/destruction/the loss property casualties/the public's facilities/the vital object/in fact eliminated the life of humankind. Terrorism was the threat for each country in whichever world was needed by efforts and the co-operation together to combat him. Indonesia basically had the standard of the law to join towards the eradication of terrorism, but is gotten by several substantive weaknesses in this terrorism act, especially that was linked with the definition and detailed classification of terrorism as well as his practical law that it was felt could show the violation of human rights. In connection with substantive weaknesses in terrorism act, was needed by several changes like more detailed the definition and criminal act limitations of terrorism and improved the law of criminal procedure system that was used, especially clarified concerning the form and limitations of beginning proof that eventually will be used as the foundation in decisive the criminal act of terrorism happened. Including also considered the TNI entry in the eradication system of terrorism in Indonesia